An axial length measurement system based on the VIPA spectrometer. (1st February 2023) - Li, Jinlu; Zhao, Shuang; Yang, Qiang; Zhou, Zhehai; Liu, Fangling; Li, Zhende; Ling, Shuaishuai
Abstract: In the ophthalmology field, the length of the eye axis is an effective way to determine whether the eye is healthy or not. Thus, the accurate measurement of the axial length becomes very important. In this paper, a measurement system for axial length based on a virtual image phase array spectrometer is planned. This system has many advantages, such as short acquisition time, wide spectrum measurement variability, high spectral resolution, etc. With the advantages of it being non-invasive and the fact that it can be used in real time, the optical coherence tomography system can be used to enhance the speed of the interference image spectrum of the cornea and retina. By verifying the effectiveness of the system, eye samples with an axis length of 18–32 mm are measured accurately with a measurement error of ±0.07 mm and a minimum measurement length of around 0.55 mm. The optical power of the incident light entering the sample at a wavelength of 810 nm is measured by an optical power meter to be less than 710 μ m, and the power of the reflected light from the sample is 95nW. Based on the data above, the measurement system in this paper is identified as a biometric instrument that complies with internationally accepted safety standards.